2013
DOI: 10.12669/pjms.292.2980
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative complication between Laryngeal Mask Airway and endotracheal tube during low-flow anesthesia with controlled ventilation

Abstract: Objective: To compare the postoperative complications between Laryngeal Mask Airway (LMA) and endotracheal tube (ETT) during low-flow anesthesia with controlled ventilation. Methodology: Eighty adult Patients with ASA class I or II were randomly allocated into two forty-patient groups (ETT or LMA). Cuff pressure was monitored during anesthesia. After high uptake period, fresh gas flow (FGF) was decreased to 1 lit/min and isoflurane set to 1%. Monitoring during anesthesia included non-invasive blood pressure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…One of these methods is the use of supraglottic devices that are designed for the lower stimulation and prevention of injuries caused by the tracheal intubation to the soft tissues, teeth, and vocal cords (4)(5)(6). It seems that due to the non-placement of laryngeal mask airway (LMA) (Figure 1) within the trachea and less irritation caused, the complications of the procedure of endotracheal intubation are less (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…One of these methods is the use of supraglottic devices that are designed for the lower stimulation and prevention of injuries caused by the tracheal intubation to the soft tissues, teeth, and vocal cords (4)(5)(6). It seems that due to the non-placement of laryngeal mask airway (LMA) (Figure 1) within the trachea and less irritation caused, the complications of the procedure of endotracheal intubation are less (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis is further supported by many other studies. Peirovifar et al (20) reported that postoperative cough, sore throat and difficulty in swallowing were significantly less in the LMA compared to the ETT group. Chun et al (19) also reported that use of the LMA in general anesthesia for thyroid surgery had advantages over the ETT in decreasing patients' subjective and objective voice symptoms, reducing the duration of symptoms, and relieving laryngopharyngeal symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies report a higher incidence of gastric insufflations and anesthetic gas leak due to low seal pressure with LMA. 9 Apart from the POST and cough, there are postoperative nausea and vomiting, hemodynamic changes were affecting the heart rate and BP associated with general anaesthesia which is also less with LMA. 10 The cause for POST and cough is not clear.…”
Section: Discussionmentioning
confidence: 99%